COMPSTAT 2004 16th symposium held in Prague, Czech Republic, 2004 : proceedings in computational statistics - Antoch, Jaromír, 1953- (Physica-Verlag, 2004)
Plné texty příspěvků mezinárodní konference o výpočetní statistice